2015
DOI: 10.1103/physrevb.92.064505
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superconductivity in heavily N- or B-doped graphene

Abstract: Two-dimensional honeycomb lattice of graphene, if heavily doped with electrons or holes, has been predicted to possess a wealth of fascinating properties including high temperature superconductivity. Although such a material is possible with high concentration of N-(or B-) substitution, its experimental realization has been hindered due to its dynamic instability. Using density functional theory combined with a global structural search and phonon dispersion calculations, we show that an ordered 50% N-(B-) dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
6
45
1
1
Order By: Relevance
“…The possibility of increasing l with doping has stimulated several recent studies, all aiming at high-T c superconductivity in graphene. Just two examples are the analysis by Zhou et al on heavily N-(electron) and B-(hole) doped graphene, 57 and the remarkable transport properties reported by Larkins et al in phosphorous-doped graphite and graphene, apparently suggesting the onset of superconductivity at temperatures as high as 260 K. 58 Among graphene systems where superconductivity is induced by the contact with a periodic Ca layer and the consequent addition of a 2D electron gas at the Fermi level, worth mentioning are the works by Yang et al where interband electron-phonon coupling is shown to play an important role, 59 and by Chapman et al on Ca-doped graphene laminates. 60 Similarly, electron-doped material such as Licovered graphene has also been predicted from first-principle calculations to attain a l value as large as 0.61 with a superconducting T c = 8.1 K. 61 Perspective PCCP Another way to induce superconductivity in graphene is the proximity effect, occurring, as demonstrated by Di Bernardo et al in a single layer graphene deposited on an oxide superconductor.…”
Section: Graphene On Metal Substratesmentioning
confidence: 99%
“…The possibility of increasing l with doping has stimulated several recent studies, all aiming at high-T c superconductivity in graphene. Just two examples are the analysis by Zhou et al on heavily N-(electron) and B-(hole) doped graphene, 57 and the remarkable transport properties reported by Larkins et al in phosphorous-doped graphite and graphene, apparently suggesting the onset of superconductivity at temperatures as high as 260 K. 58 Among graphene systems where superconductivity is induced by the contact with a periodic Ca layer and the consequent addition of a 2D electron gas at the Fermi level, worth mentioning are the works by Yang et al where interband electron-phonon coupling is shown to play an important role, 59 and by Chapman et al on Ca-doped graphene laminates. 60 Similarly, electron-doped material such as Licovered graphene has also been predicted from first-principle calculations to attain a l value as large as 0.61 with a superconducting T c = 8.1 K. 61 Perspective PCCP Another way to induce superconductivity in graphene is the proximity effect, occurring, as demonstrated by Di Bernardo et al in a single layer graphene deposited on an oxide superconductor.…”
Section: Graphene On Metal Substratesmentioning
confidence: 99%
“…For example, Pt-decorated In2O3 nanoparticles can reach up to ppb resolution 6,13 . Another way to improve the resolution of semiconductor gas sensors is to employ emerging two-dimensional (2D) materials with attractive properties such as high carrier mobility and large surface-to-volume ratios, which make them ideal materials for many applications in addition to gas sensing [14][15][16][17][18][19][20][21] . Several recent works have revealed that sensing devices based on graphene 12,22,23 or transition metal dichalcogenides (TMDs) like MoS2 24,25 can efficiently sense various gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…69 Besides that, porous C 3 N 5 , 10 C 3 N 2 , 11 C 7 N 6 , 12 and C 9 N 4 13 nanosheets have also been theoretically proposed, which possess unique electronic and topological properties as functional carbon nitrides. The hole-free structure is found to be dynamically unstable in the CN honeycomb, 14 which only appears in the C-rich case. Starting from the N-doped graphene, 2D C 1−δ N δ alloy can maintain the hexagonal lattice up to the N concentration of δ = 1/3.…”
Section: Introductionmentioning
confidence: 99%